Uniform Civil Code, Uttarakhand, 2024—Uniformizing Marriage Laws and Legalizing Live-in Relationships - Choudhary Laxmi Narayan; Mridula Narayan (Journal of Psychosexual Health)
The Uttarakhand Civil Code, 2024 has been passed by Uttarakhand Legislature and is now set to come into force after receiving Presidential assent and being notified to come into force. The Code seeks to enact a civil code applicable to all residents of the state irrespective of the religion, caste and creed of the person, except those belonging to the Scheduled Tribes. The conditions for marriage and grounds for divorce has been set in line with the Special Marriage Act, 1954. The Code provides for compulsory registration of all the marriage solemnised/ contracted within the territory of the state or performed outside the state where at least one of the parties is the resident of the state. All decree of nullity of marriage or divorce/ judicial separation are also required to be registered. Divorce in any other way than prescribed in the Code is prohibited and made punishable. Compelling or abetting any condition for divorce/ remarriage is also prohibited and punishable. One of the unique features of the Code is that it provides for legal recognition of the live-in relationships and stipulates for compulsory registration of such relationships. The Code also has provisions of protection of rights of woman in such relationships at par with a married woman. The Code also provides legitimacy to the children born out of such relationships.